Determinan Environmental Disclosure Pada Perusahaan yang Terindeks Bursa Efek Indonesia (BEI) Tahun 2021-2022 - Alifaliyudin, Achmad Torik; Purbasari, Heppy (Kompetensi (Competence : Journal of Management Studies), 2024)
The topic of how companies interact with the environment is currently quite intriguing. Research aim to examine the impact of environmental performance, company size, profitability, leverage, and company age on environmental disclosure. The study employed a quantitative descriptive method and utilized purposive sampling, focusing on companies that have published annual financial reports and are indexed by the IDX. These companies are involved in the sub-sectors of healthcare, basic materials, technology, transportation logistics, consumer non-cyclicals, industry, energy, consumer cyclicals, infrastructure, and property real estate. A total of 73 data points were collected and analyzed using multiple regression testing with SPSS v.25. The results showed that environmental performance, profitability, and company age do not significantly influence environmental disclosure, while company size and leverage do have a significant impact on environmental disclosure.